ANALISIS TARBIYAH TENTANG BERKAH RAMADHAN DAN ‘IDUL FITRI - Nurfin Sihotang (IAIN Padangsidimpuan, 2018)
This paper exsplain about the Ramadhans month as the famos time in the life of Moslem, so many worship their do in the month of Ramdhan as fasting in the noon, pray traweh in the night and reading the holy Qur’an and another worship. The writhing of this paper tray to analysis of the many worship in Ramadhan to fine the marks in moslem life from that analysis the moslems gets goods spritwal, intlektwal and emotional in them life.